2015
DOI: 10.12659/msm.895945
|View full text |Cite
|
Sign up to set email alerts
|

Rotenone Attenuates Renal Injury in Aldosterone-Infused Rats by Inhibiting Oxidative Stress, Mitochondrial Dysfunction, and Inflammasome Activation

Abstract: BackgroundReactive oxygen species (ROS) and inflammation both contribute to the progression of aldosterone-induced renal injury. To better understand the underlying mechanisms, we examined mitochondrial dysfunction and NLRP3 inflammasome activation in aldosterone-infused rats, and explored the role of rotenone in attenuating these injuries.Material/MethodsSprague-Dawley rats were divided into 3 groups: vehicle-treated, aldosterone-infused, and aldosterone plus rotenone. Renal damage was evaluated using PAS sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 28 publications
1
21
0
Order By: Relevance
“…Thus, a suitable inhibition of the activity of the injured mitochondria could restrict the release of ROS and other toxic products to attenuate the organ injury. In agreement with this concept, a number of literatures documented that the inhibition of mitochondrial complex I activity under pathological conditions protected against the organ damage [22,[34][35][36][37][38]. In the present study, we also found that mitochondrial complex I inhibitor rotenone protected against APAP-induced acute kidney injury.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, a suitable inhibition of the activity of the injured mitochondria could restrict the release of ROS and other toxic products to attenuate the organ injury. In agreement with this concept, a number of literatures documented that the inhibition of mitochondrial complex I activity under pathological conditions protected against the organ damage [22,[34][35][36][37][38]. In the present study, we also found that mitochondrial complex I inhibitor rotenone protected against APAP-induced acute kidney injury.…”
Section: Discussionsupporting
confidence: 91%
“…We previously demonstrated that mitochondrial ROS (mtROS) contribute to Aldo-induced renal tubular injury in vitro . We also showed that rotenone, an inhibitor of mitochondrial complex I, attenuated Aldo-induced renal injury by inhibiting oxidative stress and mitochondrial dysfunction [9, 10]. These results suggest MtD is an important factor in Aldo-induced kidney disease.…”
Section: Introductionmentioning
confidence: 89%
“…We cut ultrathin sections on a microtome, placed them on copper grids, stained them with uranyl acetate and lead citrate, and visualized them with an electron microscope. All these experiments were performed as described previously [10]. …”
Section: Methodsmentioning
confidence: 99%
“…Real-time PCR was performed using the ABI 7500 real-time PCR system (Applied Biosystems). The following SYBR green real-time PCR primers were used: CTGF, forward 5′-GAGGAAAACATTAAGAAGGGCAAA-3′; reverse 5′-CGGCACAGGTCTTGATGA-3′; TGF-β, forward 5′-GAGGTGACCTGGGCACCAT-3′; reverse 5′-GGCCATGAGGAGCAGGAATCCTGCTGG-3′; collagen IV, forward 5′-ATCATTGCCATCTGGAGACACCT-3′; reverse 5′-TACCATTTCTTCAACCTGGGAGC-3′; IL-1β, forward 5′-AGCCTTTGTCCTCTGCCAAGT-3′; reverse 5′-CCAGAATGTGCCACGGTTTT-3′; ATP synthase, forward 5ʹ-TCCATCAAAAACATCCAGAAAA-3ʹ; reverse 5ʹ-GAGGAGTGAATAGCACCACAAA-3ʹ; 18S, forward 5ʹ-TTCGGAACTGAGGCCATGATT-3ʹ; reverse 5ʹ-TTTCGCTCTGGTCCGTCTTG-3ʹ; and mtDNA, forward 5ʹ-TTTTATCTGCATCTGAGTTTAATCCTGT-3ʹ; reverse 5ʹ-CCACTTCATCTTACCATTTATTATCGC-3ʹ [7,23].…”
Section: Real-time Pcrmentioning
confidence: 99%
“…We had previously determined that the mitochondrial complex I inhibitor rotenone attenuated aldosterone-infused rats by inhibiting oxidative stress and MtD. The mitochondria could be the first injury target of mitochondrial-derived ROS, forming a positive pathogenic crosstalk between mitochondrial-derived ROS and MtD [7,8]. Ang II has been shown to play an important role in mitochondrial homeostasis.…”
Section: Introductionmentioning
confidence: 99%